Observations in incorporating lung ultrasound views into the echo lab: value in decompensated heart failure - Mariam B. Camacho; Samantha R. Spierling Bagsic; Santiago Camacho; James N. Phan; Bruce J. Kimura (BMC Cardiovascular Disorders)
Abstract Background Although lung ultrasound (LUS) can detect specific findings in decompensated congestive heart failure (dCHF), it is largely unavailable to hospitalized patients outside of point-of-care ultrasound practice. Therefore, we sought to determine if 4 lung views added value to echocardiography and whether LUS could be performed expeditiously in an inpatient echo lab. Methods Consecutive inpatient echo studies from a 300-bed community hospital included two posterobasal and two anteroapical lung views and were retrospectively reviewed for: (1) echo parameters including EF < 40%, E/e’>13, pseudonormal E/A ratio, among others, of which the presence of any one parameter defined an abnormal echocardiogram, Echo+, and (2) LUS bilateral findings of 3-or-more B-lines or pleural effusion defined an abnormal lung study, LUS+. Patient charts were reviewed for the clinical diagnosis of dCHF as the reference standard. Diagnostic accuracies were determined for Echo, LUS, and their combination in predicting dCHF by univariate and area under the receiver-operating characteristic (AUC) analyses. The time necessary to perform the LUS was recorded. Results Of n = 129 inpatients, mean (±SD) patient age was 67.0 ± 16.3 years, 57% were male, 32/129 (25%) had dCHF. LUS + was present in 65/129 (50%) and was related to dCHF (p < 0.0001). Despite the high 91% sensitivity of Echo + alone, the addition of LUS findings improved specificity from 49 to 89% and accuracy from 60 to 84%. Lung imaging views required only 95 s ± 42 [range: 30–227] to perform. Conclusions The addition of 4 simple lung views to the standard echocardiogram improves diagnostic accuracy for decompensated CHF without increasing imaging resources. These pilot data support integrating lung ultrasound with standard echocardiography for healthcare delivery in hospital settings.